2021
DOI: 10.1111/joim.13310
|View full text |Cite
|
Sign up to set email alerts
|

Critical COVID‐19 is associated with distinct leukocyte phenotypes and transcriptome patterns

Abstract: Background Prognostic markers for disease severity and identification of therapeutic targets in COVID‐19 are urgently needed. We have studied innate and adaptive immunity on protein and transcriptomic level in COVID‐19 patients with different disease severity at admission and longitudinally during hospitalization. Methods Peripheral blood mononuclear cells (PBMCs) were collected at three time points from 31 patients included in the Norwegian SARS‐CoV‐2 cohort study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 68 publications
4
40
0
Order By: Relevance
“…These data become even more important since the authors described an increase of mHLA-DR following corticosteroid treatment [6] . We have also described similar increase of mHLA-DR after the ex vivo treatment of monocytes with the IL-6 receptor antagonist tocilizumab [5] . These findings explain, at least partly, the mechanism of the clinical benefit provided by dexamethasone and tocilizumab in patients with SRF as this has been described in the RECOVERY and REMAP-CAP trials, respectively [ 7 , 8 ].…”
supporting
confidence: 65%
See 2 more Smart Citations
“…These data become even more important since the authors described an increase of mHLA-DR following corticosteroid treatment [6] . We have also described similar increase of mHLA-DR after the ex vivo treatment of monocytes with the IL-6 receptor antagonist tocilizumab [5] . These findings explain, at least partly, the mechanism of the clinical benefit provided by dexamethasone and tocilizumab in patients with SRF as this has been described in the RECOVERY and REMAP-CAP trials, respectively [ 7 , 8 ].…”
supporting
confidence: 65%
“…The CID of severe COVID-19 was distinct from sepsis-induced immunosuppression since PBMCs maintained their functionality for cytokine production, mainly for tumour necrosis factor-alpha (TNFα) and IL-6; in sepsis immunosuppression this functionality was lost [4] . Low mHLA-DR in severe COVID-19 has also been described in a small cohort of patients from Norway [5] .…”
mentioning
confidence: 65%
See 1 more Smart Citation
“… 140 Besides, plasma B‐cell activity and calprotectin were higher in critical COVID‐19, whereas most transcripts related to immune functions were reduced, particularly in B cells. 141 …”
Section: Application Of Transcriptomics In Covid‐19 Pandemicmentioning
confidence: 99%
“…Christensen et al reported that patients with severe Novel Coronavirus Pneumonia had higher plasma B cell activity and calprotectin levels, while transcripts related to immune function were mostly reduced, affecting B cells in particular. 6 Therefore, these data suggest a new exploratory direction for COVID-19 patient treatments in the future.…”
mentioning
confidence: 91%